Perbandingan Konsep Linguistik Ferdinand De Saussure dan Abdul Qāhir al-Jurjānī: Kajian Konseptual - Mukhotob Hamzah (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Previous scholars in linguistics study have focused only on theory proposed by European linguists, one of them is Ferdinand De Saussure from Swiss. However, long before Saussure’s concept has been popularized, in the fourth century Arab world has already had concept of linguistics initiated by Abdul Qāhir al-Jurjāni. Embarked upon a study on language construction of Al-Qur'an, he extended the concept to general context including Arabic literature. This current study compared Al-Jurjāni and Saussure theoretical concepts by employing library research. The main sources were taken from Dalailul i'jaz authored by Al-Jurjāni and Course in Gerenal Linguistics written by Charles Bally and Albert Sechehay taken from their notes in Saussure’s college class. The findings reveal the sameness of linguistics concept between Saussure and Al- Jurjāni namely langue-parole vs Lughah-Kalam, Significant-Signifier vs lafal-makna, and Syntagmatic-Paradigmatic vs an-nadzm- al-Ikhtiār.